THE ANALYSIS OF YOUTUBE GAMING CONTENT IMPACT ON CHILDRENS’ DEVELOPMENT - Ananda Fathur Rahman; Sahayu, Wening (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: The increases of the internet era have become stronger. The development of technology on the internet is marked by social media usage. This research aimed to analyze YouTube gaming contents’ impact on children’s development. The methods used in this research were descriptive methods and literature studies using socio-pragmatic analysis and transactional techniques based on a qualitative approach. Six YouTube content videos were used as object materials for analysis in this research. Researchers used socio-pragmatic analysis techniques to analyze the data. The results of the research showed that there were impolite speech acts in the behavior of streamers when presenting gaming content that affected a child’s development, and there were several negative impacts of online game addiction, such as online game syndrome and activity of slamming smartphones for online game addicts when they lose. Abstrak: Peningkatan era internet semakin kuat. Perkembangan teknologi di internet ditandai dengan penggunaan media sosial. Penelitian ini bertujuan untuk menganalisis dampak konten game YouTube terhadap tumbuh kembang anak. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dan studi literatur dengan menggunakan analisis sosio-pragmatis dan teknik transaksional berdasarkan pendekatan kualitatif. Enam video konten YouTube digunakan sebagai bahan objek analisis dalam penelitian ini. Peneliti menggunakan teknik analisis sosiopragmatik untuk menganalisis data. Hasil penelitian menunjukkan bahwa terdapat tindak tutur tidak sopan pada perilaku streamer saat menyajikan konten game yang mempengaruhi tumbuh kembang anak, serta terdapat beberapa dampak negatif dari kecanduan game online seperti sindrom game online dan aktivitas membanting ponsel untuk pecandu ketika mereka kalah.